MODEL DAN MEDIA PEMBELAJARAN BAGI SISWA SD UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI: Literatur Review - Sakrim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This research aims to determine learning models and media for elementary school students to improve their poetry writing skills. This research is a literature review type. The sample used in this research was limited to elementary school students. The articles in this research were obtained from Google Scholar with the keywords learning models for elementary school students to improve poetry writing skills. The literature review in this research includes methods, samples. results, and conclusions. The results of this research show that 8 articles from Google Scholar were found that were suitable. The conclusion of this research is that learning models to improve poetry writing skills include the Project Based Learning Model, Synectic Learning Model, and Acrostic Technique. Media to improve poetry writing skills include Audio Visual Media, Experiential Learning Assisted by Image Media, Image Media, Big Book Media, and Diorama Media.